Measurement of range-of-motion in infants with indications of upper cervical dysfunction using the Flexion-Rotation-Test and Lateral-Flexion-Test: a blinded inter-rater reliability study in a clinical practice setting. (2nd January 2021) - Driehuis, Femke; Keijsers, Noël L.W.; Nijhuis–van der Sanden, Maria W.G.; De Bie, Rob A.; Staal, J. Bart; Hoogeboom, Thomas J.
ABSTRACT: Background : In infants with indications of upper cervical dysfunction, the Flexion-Rotation-Test and Lateral-Flexion-Test are used to indicate reduced upper cervical range-of-motion (ROM). In infants, the inter-rater reliability of these tests is unknown. Objective : To assess the inter-rater reliability of subjectively and objectively measured ROM by using the Flexion-Rotation-Test and Lateral-Flexion-Test. Methods : 36 infants (<6 months) and three manual therapists participated in this cross-sectional observational study. Pairs of two manual therapists independently assessed infants' upper cervical ROM using the Flexion-Rotation-Test and Lateral-Flexion-Test, blinded for each other's outcomes. Two inertial motion sensors objectively measured cervical ROM. Inter-rater reliability was determined between each pair of manual therapists. For subjective outcomes, Cohen's kappa (ĸ) and the proportion of agreement (Pr a) were calculated. For objectively measured ROM, Bland Altman plots were conducted and Limits of Agreement and Intraclass Correlation Coefficients (ICC) were calculated. Results : The inter-rater reliability of the Flexion-Rotation-Test and Lateral-Flexion-Test for subjective (ĸ: 0.077–0.727; Pr a : 0.46–0.86) and objective outcomes (ICC: 0.019–0.496) varied between pairs of manual therapists. Conclusion : Assessed ROM largely depends on the performance of the assessment and its interpretation by manual therapists, leading to high variation in outcomes. Therefore, the Flexion-Rotation-Test and Lateral-Flexion-Test cannot be used solely as a reliable outcome measure in clinical practice and research context.